Indentation and overall compression behavior of multilayered thin-film composites: Effect of undulating layer geometry. (February 2016) - Jamison, Ryan D; Shen, Yu-Lin
Two finite element models are used to investigate the behavior of aluminum/silicon carbide thin-film layered composites with imperfect internal geometry when subjected to various loadings. In both models, undulating layers are represented by regular waveforms with various amplitudes, wavelengths, and phase offsets. First, uniaxial compressive loading of the composite is considered. The modulus and stress/strain response of the composite is sensitive to both loading direction and frequency of the undulation. Second, the nanoindentation response of the composite is investigated. The derived hardness and modulus are shown to be sensitive to the presence of undulating layers and the relative size of the indenter to the undulation. Undulating layers create bands of tensile and compressive stress in the indentation direction that are significantly different from the flat layers. The amount of equivalent plastic strain in the Al layers is increased by the presence of undulating layers. The correlations between the two forms of loading, and the implications to composite property measurement are carefully examined in this study.